Pathogenesis of Graves’ Disease Determined Using Single-Cell Sequencing with Thyroid Autoantigen Peptide Stimulation in B Cells - Genki Kobayashi; Takuro Okamura; Yoshitaka Hashimoto; Kimiko Sakai; Madoka Sumi; Dan Imai; Nobuko Kitagawa; Masahide Hamaguchi; Michiaki Fukui (Cells)
This study reports the use of single-cell RNA sequencing to evaluate B cells in the peripheral blood mononuclear cells (PBMCs) and intrathyroidal blood mononuclear cells of patients with Graves’ disease (GD) undergoing thyroidectomy. These cells were stimulated with overlapping peptides of thyroid autoantigens, including thyroid-stimulating hormone receptor (TSHR), thyroglobulin (Tg), and thyroid peroxidase (TPO). In PBMCs, naive B cells are characterized by IL6 and CXCR5, whereas memory B cells express IGHG1, IGHG2, and CD74. HLA-DMA, HLA-DRB1, IGHG, IGHM, CD74, CD79A, and MS4A1 expression increased in peptide-stimulated naive and memory B cells compared to those in the controls. Thyroid naive B cells are characterized by CD40 and TNFRSF13C, whereas memory B cells express IGHM, CD79A, and MS4A1. Thyroid B cells showed higher DUSP1, DUSP2, CD69, FOSB, RGS1, and immunoglobulin gene expression than control PBMCs and thyroid cells. B-cell receptor analysis revealed frequent IGHV3-23 and IGHV4-34 usage in controls, whereas IGHV4-34/IGHJ4 expression was increased in TSHR-stimulated groups. We concluded that B-cell responses to TSHR, Tg, and TPO differed and that changes in B-cell reactivity also occurred in PBMCs and the thyroid. Additionally, IGHV3-23 and IGHV4-34 may be associated with autoantibody production in GD.